2020
DOI: 10.3390/molecules25071657
|View full text |Cite
|
Sign up to set email alerts
|

Nuphar lutea Extracts Exhibit Anti-Viral Activity against the Measles Virus

Abstract: Different parts of Nuphar lutea L. (yellow water lily) have been used to treat several inflammatory and pathogen-related diseases. It has shown that Nuphar lutea extracts (NUP) are active against various pathogens including bacteria, fungi, and leishmanial parasites. In an effort to detect novel therapeutic agents against negative-stranded RNA (- RNA) viruses, we have tested the effect of a partially-purified alkaloid mixture of Nuphar lutea leaves on the measles virus (MV). The MV vaccine’s Edmonston strain w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…Similar investigations on the medicinal potentials of Nuphar extracts showed anti-bacterial activity [15]. Another study carried out on the extract of Nuphar lutea showed inhibitory effects on some bacteria [16,17] and against pathogenic fungi [18].…”
Section: Figure 4 Antioxidant Effects Of Crude Extracts Of Fungal End...mentioning
confidence: 59%
“…Similar investigations on the medicinal potentials of Nuphar extracts showed anti-bacterial activity [15]. Another study carried out on the extract of Nuphar lutea showed inhibitory effects on some bacteria [16,17] and against pathogenic fungi [18].…”
Section: Figure 4 Antioxidant Effects Of Crude Extracts Of Fungal End...mentioning
confidence: 59%
“…The antiviral property against MV was quantified by using qRT-PCR and the IC 50 value was determined (0.3 μg/mL). The authors also claim the inhibitory activity of the methanolic extract against Respiratory Syncytial Virus (RSV) [ 161 ].…”
Section: Antiviral Activity From Plant Extracts and Secondary Metabolitesmentioning
confidence: 99%
“…Natural products of Nuphar lutea (L.) Sm. (Nymphaeaceae) have been widely used for treating inflammatory conditions in ethnic medicine [ 1 , 2 ]. A systematic review of early studies revealed that the full therapeutic potential of Nuphar products is still largely unexplored by modern research [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…(NUP), is enriched in sesquiterpene thioalkaloids, such as nupharidine and bi-nupharidine isomers [ 4 ]. A variety of therapeutic applications have been described: anti-inflammatory [ 2 ], antibacterial [ 5 , 6 ], antiviral [ 1 ], against pathogenic fungi [ 7 ], against leishmania, and trypanosome parasites, [ 8 , 9 , 10 ], and against cancer. We previously examined the effect of NUP extracts in B16 melanoma, experimental murine lung metastasis model, and in a variety of cell lines, demonstrating its ability to affect ERK and NF-κB pathways.…”
Section: Introductionmentioning
confidence: 99%